Validation of an experimental technique with the physically based global method - Magiera, Jacek (Computer Assisted Methods in Engineering and Science, 2017)
Validation of an experimental approach requires that both model and data errors are proved to be within acceptable ranges. In case of destructive testing none of the classic, statistically based methods can be applied for that task due to the lack of independent data series required for building data statistics. The aim of the paper is to present a non-statistical methodology for performing such validation, developed within the framework of physically based approximation (PBA). It has been developed to validate a neutron diffraction based experimental-numerical approach applied for studying 3D rail residual stress. It is for the PBA technique's capability to provide high quality physically reasonable data fits for one data set only, treated here as higher order reference fields that made it possible to develop this methodology and perform error analysis/validation. In many ways this approach is analogical to Zienkiewicz-Zhu type of error estimators, and its performance will be demonstrated for a defective RE136 rail sample that was installed in a US DOT test track.